Prevalence and clinical correlates of ambulatory blood pressure phenotypes in a Saudi hypertensive population. Issue 12 (23rd September 2020) - Mahmud, Azra; Alahaideb, Ruba; Alshammary, Haifa; Abanumay, Mayar; Alfawwaz, Afnan; Alhelabi, Sara; Alonazy, Amgad; Al‐Zaibag, Muayed
Abstract: International Guidelines recommend ambulatory blood pressure monitoring (ABPM) for the management of hypertension. ABPM phenotypes predict outcomes independent of office blood pressure (BP). The authors explored the prevalence and clinical correlates of ABPM phenotypes and relationship with office BP in Saudi patients (n = 428, mean age 53.5 ± 14.6, 55% male) referred to a Specialist Hypertension clinic in Riyadh, Saudi Arabia. ABPM phenotypes included sustained normotension (27%), masked hypertension, MHT(32%), sustained hypertension, SHT(52%), and white coat hypertension(2.6%). MHT was more prevalent using asleep than 24‐hours (26.4% vs 12.9%, P  < .01) or awake BP (26.4% vs 8.5%, P  < .001) and observed in 85% of pre‐hypertensive patients. Isolated nocturnal hypertension was more prevalent in MHT vs SHT (70% vs 30%, P  < .001). Office BP overestimated control rates compared with ABPM (48% vs 12.9%, P  < .001). Our study shows that one in three Saudi patients will be managed inappropriately if office BP alone was relied upon for management of hypertension.